2020
DOI: 10.1523/eneuro.0507-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

RPE Cells Engulf Microvesicles Secreted by Degenerating Rod Photoreceptors

Abstract: Rhodopsin is mislocalized to the inner segment plasma membrane (IS PM) in various blinding disorders including autosomal-dominant retinitis pigmentosa caused by class I rhodopsin mutations. In these disorders, rhodopsin-laden microvesicles are secreted into the extracellular milieu by afflicted photoreceptor cells. Using a Xenopus laevis model expressing class I mutant rhodopsin or Na 1 /K 1-ATPase (NKA) fused to Dendra2, we fluorescently labeled the microvesicles and found retinal pigment epithelial (RPE) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Microvesicle release from photoreceptors was reported in vivo (Ropelewski and Imanishi, 2020). Here, we provide the first direct comparison of neuronal and glial secretomes and of the respective cell lysates.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Microvesicle release from photoreceptors was reported in vivo (Ropelewski and Imanishi, 2020). Here, we provide the first direct comparison of neuronal and glial secretomes and of the respective cell lysates.…”
Section: Discussionmentioning
confidence: 79%
“…Few studies characterized EVs secreted by other types of retinal cells in vitro including precursor cells (Zhou et al, 2018), astrocytes (Hajrasouliha et al, 2013), retinal ganglion cells (Wang et al, 2021) and photoreceptors (Kalargyrou et al, 2021). Microvesicle release from photoreceptors was reported in vivo (Ropelewski and Imanishi, 2020). Here, we provide the first direct comparison of neuronal and glial secretomes and of the respective cell lysates.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies characterized EVs secreted by other types of retinal cells in vitro including precursor cells (Zhou et al., 2018 ), astrocytes (Hajrasouliha et al., 2013 ), retinal ganglion cells (Wang et al., 2021 ) and photoreceptors (Kalargyrou et al., 2021 ). Microvesicle release from photoreceptors was reported in vivo (Ropelewski & Imanishi, 2020 ). Here, we provide the first direct comparison of neuronal and glial secretomes and of the respective cell lysates.…”
Section: Discussionmentioning
confidence: 99%
“…Why would such a mechanism exist in addition to the classical endolysosomal pathway? One possible explanation can be found in two studies of transgenic frogs expressing mutant rhodopsin ( Ropelewski and Imanishi, 2019 , 2020 ). The authors noted that both microvesicle release and endolysosomal degradation are capable of removing mutant rhodopsin from the inner segment plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, each of the proteins mutated in the latter group is implicated in supporting protein trafficking, including the trafficking of the visual pigment rhodopsin from the inner to the outer segment. A comparable vesicular accumulation around inner segments takes place in mice, rabbits, rats and frogs transgenically expressing various rhodopsin mutants ( Li et al, 1996 ; Kondo et al, 2009 ; Concepcion and Chen, 2010 ; Lodowski et al, 2013 ; LaVail et al, 2018 ; Ropelewski and Imanishi, 2020 ). It has been suggested that, at least in the case of mutant rhodopsin, this vesicular release serves as a safeguard mechanism counteracting the pathological accumulation of mislocalized protein in the inner segment ( Lodowski et al, 2013 ).…”
Section: Introductionmentioning
confidence: 86%